Cavitation dynamics and thermodynamic effect of R134a refrigerant in a Venturi tube - Beile Zhang; Ze Zhang; Xufeng Fang; Rong Xue; Shuangtao Chen; Yu Hou (Ultrasonics Sonochemistry)
Cavitation plays a crucial role in the reliability of components in refrigeration systems. The properties of refrigerants change significantly with temperature, thereby amplifying the impact of thermodynamic effects. This study, based on the Large Eddy Simulation (LES) method and the Schnerr-Sauer (S-S) cavitation model, investigates the transient cavitating flow characteristics of the R134a refrigerant in a Venturi tube (VT). The bubble number density in the S-S model was improved based on the experimental data of pressure and temperature. Simulation results indicate that there are two shedding modes of cavitation clouds in R134a refrigerant. One is induced by the combined action of reentrant flow and the vortices centrifugal force, while the other is generated by the central jet of the mainstream and the reverse jet produced by the collapsing cavitation bubbles. Furthermore, the thermodynamic effects of the refrigerant exert a certain inhibitory effect on cavitation, revealing the causes of instability in the refrigerant cavitation interface and the shedding characteristics of cavitation clouds. The relationship between local sound speed, flow velocity, and heat conduction rate in the cavitation region was studied, unveiling a time-lag in temperature changes relative to pressure changes in the intensive cavitation region. This study provides insights into the complex cavitation dynamics, especially in R134a refrigerant systems, and provides an approach for accurately predicting and managing cavitation in various industrial applications.